2021
DOI: 10.3390/app11136191
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Optical Chirality in Cellulose Nanocrystal Films Prepared by Shear-Coating

Abstract: Evaporation-induced-self-assembly is widely used to produce chiral cellulose nanocrystal (CNC) free-standing films reflecting left-handed polarized light. Research on supported chiral CNC films is rather scarce. The reflection and/or transmission of unpolarized light are the most common optical techniques used to characterize the selective reflection of CNC films whereas the use of techniques to quantify chiral properties is limited. Here, the fabrication of chiral CNC films supported on glass substrates by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The Kramers-Kronig consistency of CD and CB noticed in Figure 8b,d is also expected. To the authors' knowledge, CB of CNC chiral films is not often reported, with the exemptions of our previous works on free-standing [30] and shearcoated CNC films [42]. In the latter work, a quantification of the chirality parameter using Tellegen constitutive equations confirmed the Kramers-Kronig consistency.…”
Section: Polarization Properties Of Cnc Filmssupporting
confidence: 52%
“…The Kramers-Kronig consistency of CD and CB noticed in Figure 8b,d is also expected. To the authors' knowledge, CB of CNC chiral films is not often reported, with the exemptions of our previous works on free-standing [30] and shearcoated CNC films [42]. In the latter work, a quantification of the chirality parameter using Tellegen constitutive equations confirmed the Kramers-Kronig consistency.…”
Section: Polarization Properties Of Cnc Filmssupporting
confidence: 52%
“…First, the local shear of the cholesteric domains causes a distortion of the CNC helicoidal arrangement, which results in the reflected light having an elliptical polarisation that is still predominantly left-handed, i.e. that can be decomposed in a main left-circularly polarised (LCP) component as well as a small right-circularly polarised (RCP) component 12 , 31 . Second, at a larger scale the buckling of the interface results in highly tilted cholesteric regions, effectively acting as birefringent retardation plates.…”
Section: Resultsmentioning
confidence: 99%
“…Thorough investigations on the reflective color and cholesteric pitch are carried out by tuning temperature, 17 sonication, 18 homogenization, 19 electromagnetic interference, 20 and substrate 21,22 as well as surface charge density, 23,24 ionic strength, 25 compatibility, 26 or dopants. 27,28 In addition, in a dynamic drive of an inductive field of a highvoltage electric field, 29,30 high-speed spinning, 31 or linear shearing, 22,32,33 the chiral nematic structure of CNCs became unstable, resulting in a somewhat alteration or brokage of chiral orientation or long-range twisting order. In our previous work, several approaches of increasing colloidal concentration, raising cast temperature, or slowing down shearing speed were adopted to maintain the sustainability of cholesteric chiroptical properties of CNCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Along with a slow water evaporation, chiral nematic mesophases of colloidal CNCs are self-assembled into a form of spherical, ellipsoidal, or spindle-shaped tactoids, which tend to merge into continuous anisotropic phases under the hydrodynamic drives. In a continuous precipitation of chiral nematic layers, layer distance, rotation angle of the plane, and periodic anchoring are all crucial to determine or influence the chiroptical wavelength, bandwidth, reflectivity, and structural color of CNCs. Thorough investigations on the reflective color and cholesteric pitch are carried out by tuning temperature, sonication, homogenization, electromagnetic interference, and substrate , as well as surface charge density, , ionic strength, compatibility, or dopants. , In addition, in a dynamic drive of an inductive field of a high-voltage electric field, , high-speed spinning, or linear shearing, ,, the chiral nematic structure of CNCs became unstable, resulting in a somewhat alteration or brokage of chiral orientation or long-range twisting order. In our previous work, several approaches of increasing colloidal concentration, raising cast temperature, or slowing down shearing speed were adopted to maintain the sustainability of cholesteric chiroptical properties of CNCs …”
Section: Introductionmentioning
confidence: 99%